2000
DOI: 10.1152/ajpheart.2000.279.4.h1786
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of endothelium and smooth muscle function in monocrotaline-induced pulmonary hypertensive arteries

Abstract: We examined how monocrotaline (MCT), which impairs the endothelium and causes pulmonary hypertension, altered the endothelial regulation of pulmonary artery functions. Rats were given a single injection of MCT (60 mg/kg sc). Pulmonary arteries were depolarized to -48.3 +/- 2.6 and -39.8 +/- 2.2 mV at 2 and 3 wk after treatment with MCT, respectively (control arteries -59.9 +/- 1.9 mV). The basal tone in the resting state was only slightly elevated at 3 wk in endothelium-intact arteries. Removal of the endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 34 publications
5
30
1
2
Order By: Relevance
“…33,34 Although the pathogenesis and pathophysiology of this model cannot be considered identical to all forms of human PAH, the MCT-induced PAH model shows endothelial injury and dysfunction, which is generally seen in human PAH. 35 We still need to investigate, however, whether our findings in this model can be reproducible in other PAH models.…”
Section: Limitations Of This Studymentioning
confidence: 88%
“…33,34 Although the pathogenesis and pathophysiology of this model cannot be considered identical to all forms of human PAH, the MCT-induced PAH model shows endothelial injury and dysfunction, which is generally seen in human PAH. 35 We still need to investigate, however, whether our findings in this model can be reproducible in other PAH models.…”
Section: Limitations Of This Studymentioning
confidence: 88%
“…MCT-induced pulmonary hypertension is a well-known experimental model of pulmonary vascular disease that has an important inflammatory component [19]. MCT causes endothelial injury and subsequent endothelial dysfunction of pulmonary arteries [20]. Impaired endothelium-dependent relaxation is caused by endothelial dysfunction and/or reduced vasodilator function in vascular smooth muscle.…”
Section: Vascular Tonementioning
confidence: 99%
“…For example, PASMCs are continuously depolarized and accordingly cytosolic Ca 2+ levels increase (41). Ito et al found that increments of the basal active tonus of pulmonary artery in monocrotaline-induced pulmonary hypertensive rat are associated with membrane depolarization (42,43). Although the depolarization mechanism is not fully understood, Cl − -channel activation can partly explain it (24,44).…”
Section: +mentioning
confidence: 99%